ATF6β‐based fine‐tuning of the unfolded protein response enhances therapeutic antibody productivity of Chinese hamster ovary cells. Issue 6 (June 2017) - Pieper, Lisa A.; Strotbek, Michaela; Wenger, Till; Olayioye, Monilola A.; Hausser, Angelika
ABSTRACT: The dynamics of protein folding and secretion are key issues in improving the productivity and robustness of Chinese hamster ovary (CHO) producer cells. High recombinant protein secretion in CHO producer clones triggers the activation of the unfolded protein response (UPR), an intracellular response to the accumulation of unfolded and misfolded proteins in the endoplasmic reticulum (ER). We previously reported that the human microRNA (miRNA) miR‐1287 enhances productivity in IgG‐expressing CHO cells (CHO‐IgG). Here, through next‐generation sequencing (NGS), we identified the activating transcription factor 6 beta (ATF6β), a repressor of the pro‐survival and UPR promoting factor ATF6α, as a direct target gene of miR‐1287 in CHO‐IgG cells. We show that the transient depletion of ATF6β resulted in enhanced specific productivity comparable to that of miR‐1287‐expressing CHO‐IgG cells. Strikingly, stable  ATF6β knockdown in CHO‐IgG cells significantly improved antibody titer and viable cell density under fed‐batch conditions. This was associated with the elevated expression of the UPR genes glucose‐regulated protein 78 (GRP78), homocysteine inducible ER protein with ubiquitin like domain 1 (Herpud1) and CCAAT/enhancer‐binding protein homologous protein (CHOP). We hence demonstrate that ATF6β‐based cell line engineering is a promising strategy to improve the productivity of CHO producer cells by activating an optimally balanced UPR program. Biotechnol. Bioeng. 2017;114: 1310–1318. © 2017 Wiley Periodicals, Inc.